Asas Ne Bis In Idem dalam Penegakan Hukum di Indonesia: Analisis Komparatif antara Sitem Hukum Indonesia dan Prancis - Rakha Ahmad Rabani (AL WASATH Jurnal Ilmu Hukum, 2026)
The principle of ne bis in idem is a fundamental concept in criminal law that ensures legal certainty and protects human rights from repeated prosecution for the same act. This study aims to conduct a comparative analysis of the application of the ne bis in idem principle within the criminal justice systems of Indonesia and France, as well as its implications for legal certainty and the protection of human rights. The methodology employed in this research is normative legal research, utilizing legislative, conceptual, and comparative approaches. The findings indicate that the application of the ne bis in idem principle in Indonesia still faces various challenges, both normative and practical, primarily due to overlapping legal regimes and inconsistencies in interpretation. In contrast, France applies this principle more consistently through the harmonization of national law with European Union law. This study underscores the importance of strengthening the application of the ne bis in idem principle in Indonesia to ensure legal certainty and a fair legal process.